Truth, politics, morality : pragmatism and deliberation - Misak, C. J. (Cheryl J.) (Routledge, 2000)
Cheryl Misak argues that truth ought to be reinstated to a central position in moral and political philosophy. She argues that the correct account of truth is one found in a certain kind of pragmatism: a true belief is one upon which inquiry could not improve, a belief which would not be defeated by experience and argument. This account is not only an improvement on the views of central figures such as Rawls and Habermas, but it can also make sense of the idea that, despite conflict, pluralism, and the expression of difference, our moral and political beliefs aim at truth and can be subject to criticism. Anyone interested in a fresh discussion of political theory and philosophy will find this a fascinating read.